The 'Old New Russian Town': Modernization and Architectural Preservation in Russia's Historic North West, 1961-1982. (1st April 2013) - Donovan, Victoria
Abstract : The emergence of a Soviet preservationist movement, which gained institutional coherence in the mid-1960s, appears to stand at odds with the ideas of rationalization and standardization that informed the Khrushchev-era urban development programme. Yet, as I argue in this article, these two strands of post-Stalin era Soviet culture were not as antagonistic as they may first appear. In Khrushchev's Russia, the preservation of architectural heritage was rationalized as a means of strengthening the foundations of Soviet society by rooting it in the national past. Rather than detracting from the goal of building communism, cultural heritage was made an integral part of that process, a focus of national pride and source of social solidarity.